The Influence of Agile Leadership, Employee Resilience, and Organizational Commitment on Organizational Performance, PT. Industri Jamu Dan Farmasi Sido Muncul, Tbk - Maria Fenina Indah Berliana; Pitaloka Dharma A; Nurmiyati Nurmiyati (MANAJEMEN, 2025)
This research aims to analyze the effect of Leadeship Agility, Employee Resilience, and Organizational Commitment on Organizational Performance at PT. Industri Jamu dan Farmasi Sidomuncul, Tbk.  Organizational Performance is identified as the dependent variable, while the independent variables include agile leadership, employee resilience, and organizational commitment. This research employs a quantitative method with a survey approach. Data were collected from a population and sample of 100 employees, using a questionnaire. The data were analyzed using Partial Least Square (PLS) method with SmartPLS 3.0 software. The research results show that 1) Leadership Agility has an impact on Organizational Performance, 2) Employee Resilience has a significant positive effect, and 3)  Organizational Commitment does not have a significant effect on Organizational Performance.